Prediction of Re-positivity for Coronavirus Nucleic Acid Among COVID-19 Patients in the Recovery Phase - Zhu, Shu-fen; Sun, Bo; Li, Jin-kuang; Cai, Yue; Li, Peng-fei; Hong, Ji-chang; Li, Jin-hai; Xu, Shi-wen; Li, Xiao-yang; Xue, Chen-wei; Gu, Bin-bin; Wu, Jian-fen; et al. (Frontiers in Medicine, 2021)
Background and Objectives: Although the pathogenesis and treatment of coronavirus disease 2019 (COVID-19) have been gradually revealed, the risk for re-emergence of coronavirus nucleic acids in recovered patients remains poorly understood. Hence, this study evaluated the risk predictors associated with re-positivity for virus nucleic acid. Methods: Between February 1 and March 20, 2020, we retrospectively reviewed the clinical epidemiological data of 129 COVID-19 patients who were treated at Zhongxiang People’s Hospital of Hubei Province in China. Subsequently, a risk prediction model for the re-positivity of virus nucleic acid was developed, and a receiver operating characteristic (ROC) curve was drawn for further validation. Results: In this study, the rate of re-positivity for virus nucleic acid was 17.8% (23/129) where all re-positivity cases were asymptomatic. The median time interval from discharge to nucleic acid re-positivity was 11.5 days (range: 7–23 days). Multivariate logistic regression analysis showed that leukocytopenia (odds ratio [OR] 7.316, 95% confidence interval [CI] 2.319–23.080, p=0.001), prealbumin <150 mg/L (OR 4.199, 95% CI 1.461–12.071, p=0.008), and hyperpyrexia (body temperature >39 °C, OR 4.643, 95% CI 1.426–15.117, p=0.011) were independent risk factors associated with re-positivity. The area under the ROC curve was 0.815 (95% CI, 0.729–0.902). Conclusion: COVID-19 patients with leukocytopenia, low prealbumin level, and hyperpyrexia are more likely to test positive for virus nucleic acid after discharge. Timely and effective treatment and appropriate extension of hospital stays and quarantine periods may be feasible strategies for managing such patients.